Helium on Mars - J.-Y. Chaufray; F. Gonzalez-Galindo; R. Modolo; F. Leblanc; F. Forget; J. Liu; E. Millour; M. Lopez-Valverde; V. Steichen; G. Chanteur (Icarus, 2026)

No theoretical basis for an orbit–spin coupling inertial force in planetary atmospheres - T. Pierron; F. Forget (Icarus, 2026)

Tuna aggregation dynamics in an array of anchored fish aggregating devices (AFADs) - D. Thambithurai; A.R. Jauharee; Y. Baidai; F. Forget; A. Dupaix; M.S. Adam; L. Dagorn; M. Capello (Fisheries Research, 2025)

Modelling the effect of volcanic outgassing of sulphur on early Martian surface temperatures using a 3-D Global Climate Model - A.S. Braude; L. Kerber; F. Lefèvre; A.Y. Jaziri; S.S. Hamid; M. Lefèvre; M. Maurice; E. Millour; F. Forget (Icarus, 2025)

North Atlantic Heat Transport Convergence Derived from a Regional Energy Budget Using Different Ocean Heat Content Estimates - B. Meyssignac; S. Fourest; Michael Mayer; G. C. Johnson; F. M. Calafat; M. Ablain; T. Boyer; L. Cheng; D. Desbruyères; G. Forget; D. Giglio; M. Kuusela; et al. (Surveys in Geophysics, 2024)
This study uses an oceanic energy budget to estimate the ocean heat transport convergence in the North Atlantic during 2005–2018. The horizontal convergence of the ocean heat transport is estimated using ocean heat content tendency primarily derived from satellite altimetry combined with space gravimetry. The net surface energy fluxes are inferred from mass-corrected divergence of atmospheric energy transport and tendency of the ECMWF ERA5 reanalysis combined with top-of-the-atmosphere radiative fluxes from the clouds and the Earth’s radiant energy system project. The indirectly estimated horizontal convergence of the ocean heat transport is integrated between the rapid climate change-meridional overturning circulation and heatflux array (RAPID) section at 26.5°N (operating since 2004) and the overturning in the subpolar north atlantic program (OSNAP) section, situated at 53°–60°N (operating since 2014). This is to validate the ocean heat transport convergence estimate against an independent estimate derived from RAPID and OSNAP in-situ measurements. The mean ocean energy budget of the North Atlantic is closed to within ± 0.25 PW between RAPID and OSNAP sections. The mean oceanic heat transport convergence between these sections is 0.58 ± 0.25 PW, which agrees well with observed section transports. Interannual variability of the inferred oceanic heat transport convergence is also in reasonable agreement with the interannual variability observed at RAPID and OSNAP, with a correlation of 0.54 between annual time series. The correlation increases to 0.67 for biannual time series. Other estimates of the ocean energy budget based on ocean heat content tendency derived from various methods give similar results. Despite a large spread, the correlation is always significant meaning the results are robust against the method to estimate the ocean heat content tendency.

Simulations of the hydrogen and deuterium thermal and non-thermal escape at Mars at Spring Equinox - J.-Y. Chaufray; F. Gonzalez-Galindo; F. Leblanc; R. Modolo; M. Vals; F. Montmessin; F. Lefèvre; F. Forget; M. Lopez-Valverde; G. Gilli (Icarus, 2024)

Large-scale movements and site fidelity of two bull sharks Carcharhinus leucas estimated from a double-tagging experiment at Réunion Island (southwest Indian Ocean) - M Soria; Y Tremblay; A Blaison; F Forget; E Crochelet; L Dagorn (African Journal of Marine Science, 2021)

Beta diversity of pelagic assemblages at fish aggregating devices in the open ocean - F Forget; L Dagorn; B Mérigot; JC Gaertner; J Robinson; PD Cowley; MS Adam; Y Rilwan; M Koonjul; V Mangar; M Taquet; F Ménard (African Journal of Marine Science, 2020)

On the Future of Argo: A Global, Full-Depth, Multi-Disciplinary Array - Dean Roemmich; Matthew H. Alford; Hervé Claustre; Kenneth Johnson; Brian King; James Moum; Peter Oke; W. Brechner Owens; Sylvie Pouliquen; Sarah Purkey; Megan Scanderbeg; Toshio Suga; et al. (Frontiers in Marine Science, 2019)

Connectivity between marine reserves and exploited areas in the philopatric reef fish Chrysoblephus laticeps (Teleostei: Sparidae) - P. R. Teske; F. R. G. Forget; P. D. Cowley; S. von der Heyden; L. B. Beheregaray (Marine Biology, 2010)

Acidic pH as a determinant of TRI gene expression and trichothecene B biosynthesis in Fusarium graminearum - J. Merhej; A.L. Boutigny; L. Pinson-Gadais; F. Richard-Forget; C. Barreau (Food Additives & Contaminants: Part A, 2010)

Impact of durum wheat milling on deoxynivalenol distribution in the outcoming fractions - G. Ríos; N. Zakhia-Rozis; M. Chaurand; F. Richard-Forget; M.F. Samson; J. Abecassis; V. Lullien-Pellerin (Food Additives & Contaminants: Part A, 2009)

The expression of Rho proteins decreases with human brain tumor progression: Potential tumor markers - Marie-Annick Forget; Richard R. Desrosiers; Rolanda F. Del Maestro; Robert Moumdjian; Daniel Shedid; France Berthelet; Richard Béliveau (Clinical & Experimental Metastasis, 2002)